Stealing fire : how Silicon Valley, the Navy SEALS, and maverick scientists are revolutionizing the way we live and work /: how Silicon Valley, the Navy SEALS, and maverick scientists are revolutionizing the way we live and work. ([2017]) - Kotler, Steven, 1967-; Wheal, Jamie
No abstract available